Effects of different coffee extracts on the egg fertility and lifespan of dengue vectors (Aedes albopictus and Aedes aegypti) (diptera: culicidae) - Siti Salbiah Ellias,; Hamady Dieng,; Abdul Hafiz Ab Majid, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
This study was conducted to examine the impacts of various extracts of coffee on the egg production aedes fertility and adult lifespan in two dengue vectors. Coffee is known for its chemical richness that is so far no resistance in insects was documented. For this purpose, two types of extracts (crude and used) from two types of coffee (fresh and roasted) of Coffea canephora (Robusta coffee) were used. We compared the effects of the extracts on the egg hatching responses and the longevity of dengue vectors; Aedes albopictus and Aedes aegypti. Overall, the roasted coffee extracts tend to have more negative impact than the fresh coffee extracts in reducing the hatching success. Crude extracts of both fresh/green and roasted coffee seems to exerts more chemicals and appears to be more acidic than the used extracts in which resulted in reduced rate of larval eclosion. Longevity statistically has no difference among coffee extracts However, based on the overall observation on the longevity of the adult and the difference in the longevity suggested that the exposure of the coffee to the dengue vectors during the embryogenesis does reduces the longevity of the survived adult by few days difference.